Effects of tetracycline-containing gel and a mixture of tetracycline and citric acid-containing gel on non-surgical periodontal therapy - Renny Paul George; Saravana Kumar; T Ramakrishna; Pamela Emmadi; N Ambalavanan (Wolters Kluwer Medknow Publications, 2013)
Aims and Objectives: The purpose of this study was to assess the clinical and microbiological effects of a newly developed root-conditioning gel system containing tetracycline and a mixture of tetracycline and citric acid on non-surgical periodontal therapy. Materials and Methods: Four anterior teeth from four quadrants with a probing depth of 4-6 mm, in each of the 20 subjects with chronic periodontitis, were subjected to four different modalities of treatment. A total of 80 teeths were divided into four groups of 20 teeth each taken from separate quadrants, on the basis of one of the following four treatments: (1) Root planning alone in first quadrant (RP group); (2) tetracycline-containing gel in the second quadrant (TCG group); (3) root planning plus tetracycline-containing gel in third quadrant (RP + TCG group); (4) root planning plus a mixture of tetracycline and citric acid-containing gel in fourth quadrant (RP + TC-CAG group). Plaque index (PI), sulcular bleeding index, probing pocket depth, and clinical attachment level were measured for 0 day, 8 th week, and 12 th week, respectively. Subgingival plaque samples from each site were collected at the same visits and examined with dark field microscope for proportions of motile rods and spirochetes. Results: From 0 day to 12 th week, PI, sulcular bleeding index, probing pocket depth, and clinical attachment levels decreased significantly in all the groups. From 0 day to 12 th week, RP + TC-CAG group showed a significantly higher change in the PI score. From 0 day to 12 th week, RP group showed a significantly higher change in sulcular bleeding index score. A significant decrease in probing pocket depth and gain in clinical attachment level was noted at 12 th week in RP + TC-CAG group compared to the other groups. A significant decrease in the proportion of motile rods was found primarily in the RP + TC-CAG group. There was a decrease in the proportion of spirochetes in all the groups. Conclusion: The results indicated that the use of a mixture of tetracycline and citric acid-containing gel was effective in improving gingival health and in changing subgingival microflora.